2003
DOI: 10.1088/0022-3727/36/17/320
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of extinction, refraction and absorption properties in diffraction enhanced imaging

Abstract: Diffraction enhanced imaging is a radiographic technique that derives contrast from an object's x-ray absorption, refraction gradient and small angle scatter properties (extinction). In prior work, images obtained using two analyser settings were combined to obtain refraction angle and apparent absorption images. A more general method of determining independently the refraction, absorption and extinction of the object is presented. This approach has been used to model the transmission, refraction and scatter d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 13 publications
0
94
0
1
Order By: Relevance
“…Dilmanian et al [7] showed that DEI can be used in a computed tomography mode and that the DEI-CT data could be reconstructed using conventional filtered-backprojection (FBP) algorithms. Oltulu et al [5] and Wernick et al [6] showed that the absorption, single-refraction, and multiple-refraction signals can be separated and that CT image sets for each signal can be independently reconstructed with FBP [8]. Kitchen et al [9] and Khelashvili et al [10] showed that the origin of the angular spreading of the X-ray beam was multiple-refractions of the beam.…”
Section: Proof-of-principle Dei Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dilmanian et al [7] showed that DEI can be used in a computed tomography mode and that the DEI-CT data could be reconstructed using conventional filtered-backprojection (FBP) algorithms. Oltulu et al [5] and Wernick et al [6] showed that the absorption, single-refraction, and multiple-refraction signals can be separated and that CT image sets for each signal can be independently reconstructed with FBP [8]. Kitchen et al [9] and Khelashvili et al [10] showed that the origin of the angular spreading of the X-ray beam was multiple-refractions of the beam.…”
Section: Proof-of-principle Dei Studiesmentioning
confidence: 99%
“…These approaches include a single-image approach [2,3], a single-refraction-focused two-image approach [1], a multiplerefraction-focused two-image approach [4], and a manyimage approach [5,6]. These approaches are referred to as: phase dispersion introscopy, diffraction-enhanced X-ray imaging, DEI, ABI, and multiple image radiography.…”
Section: Introductionmentioning
confidence: 99%
“…This method can image the refractive index gradient, absorption and another contrast mechanism unique to DEI alone, extinction or ultra-small-angle scatter contrast [4,5]. These additional contrast mechanisms of refraction and extinction have recently been shown to be extraordinarily sensitive to soft tissue and specifically in the visualization of tissue types associated with breast cancer [6].…”
Section: Diffraction-enhanced X-ray Imagingmentioning
confidence: 99%
“…The original DEI method produced X-ray refraction gradient and absorption-like images (apparent absorption) in which absorption and scatter rejection are mixed. New methods have been developed to extract independent absorption and ultra-small scatter images as well as a refraction angle image [10][11][12][13]. These methods determine independent images by acquiring and analyzing several images as the analyzer crystal is rocked in the vicinity of the Bragg peak location.…”
Section: Phase Contrast Refraction and Scattering Imagingmentioning
confidence: 99%